The Dynamics of Development of Islamic Civilization in the Reformation Period - ardini, muhammad dimas; mustikasari, diyah ayu; nasikhin, nasikhin; fihris, fihris (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2023)
The main objectives of this research are historical research on the dynamics of the development of Islamic civilization during the Reformation Period is very interesting to study. It aims to describe the history of the Development of Islamic Civilization in the Reformation Period, and there are several things that include Socio-Cultural Conditions, Government Systems, Islamic Propagation Strategies, Challenges, and Influential Figures in the History of the Development of Islamic Civilization during the Reformation Period.This study  aims to analyze the dynamics of the development of Islamic civilization during the reformation period, the method we examine using the literature method produces data that; 1.) Socio-cultural conditions during the reformation period can be said to be the worst developments because during the reformation period many Indonesian people and immigrants were ethnocentric. 2.) The system of government during the reform period can be seen from the province of South Sulawesi, known as the Kingdom of Gowa, which was led by Sultan Hasanudin with his courage against Dutch colonialism. 3.) The strategy of Islamic da'wah has developed since entering the reform era, as evidenced by the number of Muslim population. 4.) Challenge. Viewed from Sulawesi, the dynamics of the spread of Islam cannot be said to face significant challenges, because the familial approach with autoplastic and alloplastic adjustments can change kings and community leaders to become Muslims so as to form an Islamic empire. 5. Influential Figures Tahir Jalaluddin is an Indonesian scholar with expertise in astronomy and astronomy. He is a figure of the Islamic reform movement in the Malay Peninsula. This study has implications for increasing literature on the history of Indonesian Islamic civilization so that it can add to the scientific treasures of Nusantara Islam.